A metallomic, proteomic and lipidomic investigation of the malaria parasites digestive vacuole and insights into the mediators of haemozoin formation - Mohunlal, Roxanne (Department of Chemistry, 2020)
Novel and unambiguous mechanistic details of the biochemical processes that enable the most virulent form of the malaria pathogen, Plasmodium falciparum, to thrive within the human host are desperately required in order to find innovative strategies to counteract emerging parasite resistance that will inevitably render current malarial therapies obsolete. This study focused on exploring the Plasmodium falciparum metallome and investigated the mediators of haemozoin formation, an ingenious parasite-specific process critical to host immune evasion as well as parasite survival and one that is surprisingly rather contentious. In order to obtain a comprehensive view of metal distribution, the trace metal content in parasites isolated at varying time-points over the 48 h intraerythrocytic cycle were measured by ICP-MS. The trace metals detected; namely, iron, magnesium, zinc, manganese and copper, were compared to control uninfected erythrocytes. With the malaria parasite being a haematophagous organism, iron was detected as the most abundant trace metal and found to exhibit a significant increase up to 32 h into the life cycle after which the measured iron content remained relatively constant and lower than the control. This was attributed to the maximum amount of haemoglobin having been ingested at this mature trophozoite stage and the active conversion of free haem (Fe(III)PPIX) into biocrystalline haemozoin. All other trace metals exhibited 2 to 4-fold increases in metal ion content as the parasite matured and were detected in amounts higher than those found in the erythrocyte control, demonstrating uptake of these ions from the external medium. These increases coincided with specific cellular events such as cell division and enhanced parasite metabolism. Qualitative proteomic analysis of parasite material identified several metalloproteins but most significant, was the discovery of magnesium and copper transporters. Together, these findings suggest that transition metal import is essential to promote important cellular events and parasite growth and are indicative of unique parasite-specific metal transport pathways. The mediators of crystal formation were investigated by interrogating the haemozoin proteome and lipidome. Haemozoin was obtained from parasitised erythrocytes following a fractionation approach which culminated in their release from purified digestive vacuoles (DVs) following multiple freeze-thaw cycles. Isolated crystals were extensively washed with aqueous sodium acetate buffer (0.5 M, pH 5.2), detergent(4% SDS) and organic solvents (acetone/methanol) prior to base dissolution (0.1 M NaOH). Mass spectrometry was used to investigate the biomolecules occluded by haemozoin by analysing extensively washed and dissolved crystals. Haem detoxification protein (HDP), a protein currently postulated to be potent in mediating haemozoin formation in vivo, was detected in high relative abundance in the dissolved haemozoin fraction by semi-quantitative label-free proteomics. Expression and purification of recombinant soluble HDP was optimised and both soluble and refolded protein were further investigated. Characterisation by circular dichroism and fluorescence spectroscopy revealed that soluble HDP differed in conformation to its refolded counterpart. In aqueous solution (pH 7.4), UV-vis spectrophotometric titrations showed soluble and refolded HDP to bind Fe(III)PPIX in a 1:1 ratio with a Kd of 1.2 ± 0.5 µM and 0.35 ± 0.04 µM respectively. Crucially, activity studies under biomimetic conditions (pH 5.2, 37°C) demonstrated that this protein was not competent to promote β-haematin (synthetic haemozoin) formation without the incorporation of detergent. Mass spectrometry-based lipidomics identified and quantified over 400 lipids in dissolved haemozoin. Neutral lipids were found to be the dominant class comprising 90% cholesterol, 2% cholesterol esters and 0.6% acylglycerols. The detected lipids were used to prepare a model lipid blend which was found to efficiently promote β-haematin formation in yields greater than 90% in under 10 minutes and at concentrations as low as 18 µM. Crystals synthesised using the model lipid blend were found to exhibit similar morphological traits to haemozoin naturally produced by the parasite. Live-cell imaging by spinning disk confocal microscopy revealed that neutral lipid bodies localised externally from the DV or in close contact with the DV membrane but were not found in the immediate vicinity of haemozoin. β-Haematin was found to occlude labelled protein and lipid when synthesised in their presence. Furthermore, occluded biomolecules were not readily displaced from the crystal surface through simple washing with aqueous buffer (pH 5.2) but were only released upon base dissolution of crystals. Pre-formed β-haematin and haemozoin incubated with labelled biomolecules resulted in no further occlusion which demonstrated that these crystals occlude material in a manner non-exchangeable with the DV lumen, thus providing a window into the molecules present at the time and site of crystal formation. Overall, this multidisciplinary omics approach has revealed that the malaria parasite has a unique metallome which may provide promising new drug targets. Significantly, this study has unequivocally demonstrated that haemozoin occludes proteins and lipids in detectable amounts in a non-exchangeable manner with the external milieu but, crucially, lipids occluded by haemozoin are present at the time and site of formation within the DV and are potent mediators of haemozoin formation in the malaria parasite.